2017
DOI: 10.4172/2161-1165.1000298
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Obesity and Coronary Heart Disease Risk among Saudi Subjects at Madinah Region

Abstract: The study aimed to characterize the major cardiovascular risk factors using Framingham Risk Score (FRS) among Saudis. A cross-sectional study was conducted to investigate the expected 10 years FRS for cardiovascular diseases (CVD) among Saudi subjects. In the present study there was a significant association between the 10 years risk of developing CHD and BMI. The results revealed an increase in BMI contributing to significant increase in the 10 years risk of CHD among males. The overall distribution of FRS am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Ahmari et al 2017 in their study in Saudi Arabia also showed that the prevalence of CHD was signi cantly related to age and gender (22), so that the prevalence of the disease was twice as high in men than women. In other studies that calculated the risk of CHD, men were at higher risk than women (4,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 85%
“…Ahmari et al 2017 in their study in Saudi Arabia also showed that the prevalence of CHD was signi cantly related to age and gender (22), so that the prevalence of the disease was twice as high in men than women. In other studies that calculated the risk of CHD, men were at higher risk than women (4,(23)(24)(25).…”
Section: Discussionmentioning
confidence: 85%